THE ROLE OF ISLAMIC VALUES IN FAMILY RELATIONSHIPS - Ubaydullayev Shakhboz (Web of Journals Publishing, 2025)
This article sheds light on the social characteristics of family relations, their connection with values and Islamic teachings. The concepts of religion, family, and values are closely interconnected. The Islamic religion presents the family as the main place for the spiritual and physical education of a person. It is emphasized that the preservation of family values is an important factor in the succession of generations.
Keywords: Dignity, family, marriage, religion, Islam, hadith, descendants, husband and wife.